Overview History of Nederlandsch-Indie Maritime Law in Twentieth Century Batavia - Rendy Kurniawan (Historia Madania: Jurnal Ilmu Sejarah, 2019)
This study is aimed at sketching out one of the outstanding influence from Dutch to Nusantara. It was the forming of the maritime law which known as scheepvaart aangelegenheden in Batavia that becomes the focus of this study. By doing this, the Dutch government had its own regulation to control each port centralizing in Batavia. With this regulation, the Dutch government could deal with the busy ports in Nederlandsch Indie much easier than before. This study is applying a qualitative method which involves documents and law manuscript discussion. The result shows that although a number of articles in the law had strongly influenced by Nusantara’s local kingdoms, there were still many various important things. Keywords: dutch government, maritime law, local kingdom, Batavia